Designing a new concept of LC-DCP broad type bone plate - Muhammad Kamal Asyraf, Pubin (2007)
Bone plate design has evolved dramatically in recent years. The main research of the study is to improve the previous design of the Dynamic Compression Plate (DCP) broad type bone plates that was used in bone fracture as internal fixation. The DCP bone plate has been superseded by new plating system that claim a reduced interface contact between the plate and the underlying bone. It is believed that contact reduction can reduce the risk of Ischaemia - deficiency of blood in a part, usually due to functional constriction or actual obstruction of blood vessel that could lead to other side effect on the patient. To develop the new proposed design, CAD (Computer Aided Design) software is used to design and simulate the model. The interface characteristics of the actual Dynamic Compression Plate (DCP) and the new Low-Contact Dynamic Compression Plate (LC-DCP) plating systems have been analyzed using a Finite Element Analysis (FEA) software. The final result of model simulation is displayed in form of stress von Mises, and heat transfer distribution. The maximum value of von-Mises stress for the new LC-DCP is 768195.2 N/rn 2 and heat transfer distribution temperature is 57.15 °C. The LC-DCP system was consistently lower, in terms of interface contact, than the DCP in each of the CAD model tested.